2005
DOI: 10.1016/j.virol.2005.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the pseudorabies virus UL43 protein

Abstract: Among the least characterized herpesvirus membrane proteins are the homologs of UL43 of herpes simplex virus 1 (HSV-1). To identify and characterize the UL43 protein of pseudorabies virus (PrV), part of the open reading frame was expressed in Escherichia coli and used for immunization of a rabbit. The antiserum recognized in Western blots a 34-kDa protein in lysates of PrV infected cells and purified virions, demonstrating that the UL43 protein is a virion component. In indirect immunofluorescence analysis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
3
24
1
Order By: Relevance
“…However, the PrV UL43 protein was suggested to inhibit membrane fusion in the transient co-expression system involving PrV envelope glycoproteins [10]. These findings seem to contradict results obtained herein with the recombinant viruses lacking UL43 gene.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, the PrV UL43 protein was suggested to inhibit membrane fusion in the transient co-expression system involving PrV envelope glycoproteins [10]. These findings seem to contradict results obtained herein with the recombinant viruses lacking UL43 gene.…”
Section: Discussioncontrasting
confidence: 75%
“…The HSV-1 UL43 has been shown to be non-essential for virus growth in cell culture and deletion of UL43 did not impair viral replication in a mouse infection model [9]. It has been reported that Pseudorabies virus (PrV) UL43 protein strongly inhibited membrane fusion induced by the viral fusion machinery in a transient expression-fusion system [10]. Although the transient co-expression assay does not accurately model viral fusion, it is conceivable that UL43 protein may be involved in modulating membrane fusion.…”
Section: Introductionmentioning
confidence: 99%
“…2b). Although in PrV gL is not required for transport of gH (Klupp et al, 1997), cotransfection of cells with gH and gL expression plasmids enhanced the proportion of the mature, fully glycosylated, approximately 95 kDa form of WT gH (Klupp et al, 1992) compared to cells transfected with the gH plasmid alone (Fig. 2a).…”
mentioning
confidence: 88%
“…If it is deleted, plaque size is reduced by approximately 10% and viral titers are decreased by ca. 2-to 5-fold [49]. Furthermore, The DPV UL43 protein has several membrane domains, potential ability to cross a membrane several times suggesting a role in signal transduction or as ion channels, just like VZV gene 15, which corresponds to HSV-1 gene UL43, contains a periodic charge pattern similar to that found in voltage-gated ion channels [50].…”
Section: Discussionmentioning
confidence: 97%